2004
DOI: 10.1139/t04-056
|View full text |Cite
|
Sign up to set email alerts
|

Compression and consolidation characteristics of structured natural clay

Abstract: The compression and consolidation behavior of some structured natural clays are discussed. It is shown that for some structured natural clays, the relation between void ratio (e) and mean effective stress (p′) is more linear in a ln(e + ec) – ln(p′) plot (where ec is a soil parameter) than in an e – ln(p′) plot. It is proposed that for structured natural clay with a sensitivity value greater than 4, a linear ln(e + ec) – ln(p′) relation can be used in settlement and consolidation calculation. The effect of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…This method to determine hydraulic conductivity is accepted extensively (Sivapullaiah et al, 2000;Chai et al, 2004;Horpibulsuk et al, 2007;Yong et al, 2009;Watabe et al, 2011;Fan et al, 2014b), and therefore it is used in this study for relative comparison of hydraulic conductivity of various zeolite-amended clayey soil/Ca-bentonite backfills.…”
Section: Methodsmentioning
confidence: 99%
“…This method to determine hydraulic conductivity is accepted extensively (Sivapullaiah et al, 2000;Chai et al, 2004;Horpibulsuk et al, 2007;Yong et al, 2009;Watabe et al, 2011;Fan et al, 2014b), and therefore it is used in this study for relative comparison of hydraulic conductivity of various zeolite-amended clayey soil/Ca-bentonite backfills.…”
Section: Methodsmentioning
confidence: 99%
“…The CRS test has an advantage over the IL test for evaluating this non-linear characteristic. Chai et al (2004) reported that for most nonlinear e À log ó9 v relationships, in a plot of log(e þ e c ) against log ó9 v , where e c is a constant, they are very close to linear, and a model is proposed to consider the non-linear e À log ó9 v behaviour in engineering design and analysis. Figure 18 shows the variation of c v with average effective vertical stress ó9 v under different strain rates for soil samples from BH-1 at 5-5 .…”
Section: Strain-rate Effect On Compression Index (C C )mentioning
confidence: 99%
“…Compression behaviour is a fundamental aspect of soil deformation, and modelling 81 compression behaviour generally forms the base of modelling the stress-strain relationships 82 of soils (e.g., Pestana and Whittle, 1995 understanding of compression behaviour has therefore always been important to geological 89 and geotechnical engineering practice and research for many decades (e.g., Skempton, 1944; 90 Bowles, 1989; Butterfield and Baligh, 1996; Desai, 2001; and Chai et al, 2004). 91…”
mentioning
confidence: 99%